Optimizing Parenting to Grow Early Childhood Character Through Islamic Education in the Digital Era - Asnawan, Asnawan; Farid, Mohtazul; Umam, Khotibul; Shalihah, Imra’atus (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
To develop resilient and adaptable children's personalities in the digital age, this study intends to investigate the application of authoritative parenting styles in this time period and how these styles are enhanced by Islamic education. The methodology is a qualitative approach with literature reviews, examining numerous trustworthy sources about Islamic values, parenting styles, and how technology affects kids' development. According to the study's findings, children can improve their digital literacy, control technology use, and develop their mental health by supporting an authoritative parenting style that prioritizes a healthy mix of affection and discipline. This parenting approach is most suited to Islamic principles, giving them a strong moral basis and assisting them in navigating the problems of the digital world responsibly. By the needs of the times, this method not only helps kids achieve academically but develops strong, moral character.